Long-term corrosion of HTGR graphite with SiC coating - Zaurbekova, Zh.A.; Blynskiy, P.A.; Chikhray, Ye.V.; Askerbekov, S.K.; Tolenova, A.U.; Kenzhina, I.Ye.; Bushnev, P.A. (Recent Contributions to Physics, 2022)
When creating a Kazakhstani high-temperature gas-cooled reactor (HTGR), a type of fuel with improved graphite and its gradient protective coating based on silicon carbide (SiC) will be used. So, the purpose of this work is determination the rate and features of the long-term high-temperature corrosion of reactor graphite and its SiC coating at a temperature of 1200K and a pressure of 200-250 kPa in helium with an admixture of water and oxygen in concentrations close to the normal operation of an HTGR; development a numerical model of a corrosion experiment with the convection method of supplying the working mixture. As a result, four successive test stages lasting 30 days each (the total duration of corrosion was 120 days), the weight loss of pure graphite samples (without SiC coating) range from 1.8% to 10.4%, depending on the manufacturer. In general, the average corrosion rate of unprotected graphite corresponds to the literature data. The use of a SiC coating over graphites reduces the corrosion rate of samples by a factor of 100-500. The developed model made it possible to describe both the high-temperature corrosion processes of HTGR graphite and the dynamics of the mass transfer of all gas components throughout the entire volume of the installation during the experiment.